1999
DOI: 10.1016/s0013-7944(98)00081-2
|View full text |Cite
|
Sign up to set email alerts
|

Crack growth in the presence of limited creep deformation

Abstract: Creep crack growth tests have been conducted on a plain carbon manganese steel, aluminium alloy 2519 and titanium alloy 6242 at 360, 135 and 500°C, respectively, at conditions where only limited creep deformation was observed. The results have been analysed using ASTM Standard E1457-92 which was developed for describing creep crack growth in the presence of extensive creep. It has been found that the creep fracture mechanics parameter C* defined in E 1457 can also be used to interpret the data 1 2 generated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In accordance w ith [19], t'in is the tim e from the instant o f load application to the crack increm ent by 0.2 m m , w hich can be determ ined approxim ately using the technique described earlier [14]. In addition, this m agnitude o f the increm ent corresponds to the onset o f the steady-state grow th o f the creep crack, as noted by m any researchers [4,16,19].…”
mentioning
confidence: 90%
“…In accordance w ith [19], t'in is the tim e from the instant o f load application to the crack increm ent by 0.2 m m , w hich can be determ ined approxim ately using the technique described earlier [14]. In addition, this m agnitude o f the increm ent corresponds to the onset o f the steady-state grow th o f the creep crack, as noted by m any researchers [4,16,19].…”
mentioning
confidence: 90%
“…The limits set in equation (4) can be practically utilised to identify the relative limits of the applicability of the parameter C* [5,12]. It is found that creep crack growth rate a & can be correlated satisfactorily in terms of C* by the relation [11,12] …”
Section: Model For Creep Crack Growthmentioning
confidence: 99%
“…For plane stress conditions the appropriate failure strain * f ε is taken to be the uniaxial failure strain, ε f , and for plane strain situations * f ε can be as low as ε f /30 [11][12]. Experimentally it has been shown that the upperbound of 30 is conservative for most creep ductile situations.…”
Section: Model For Creep Crack Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…A crack extension at high temperatures under susas engineering materials especially for high-temperature tained load is characterized by an incubation period, a period structural applications, thanks to beneficial attributes, such of decreasing crack growth rates ("transient regime"), a period as low density and high high-temperature strength and moduof steady-state crack growth rate, and final failure. [12][13][14][15][16][17][18][19][20][21][22][23][24] In lus retention, as well as advances in processing. [1][2][3][4] For the creep-brittle materials, [14,18,21,23] it has been shown that the last 10 years, low-temperature property evaluations have incubation period and the transient regime can be quite a been extensive worldwide; however, the increasing need substantial portion of the total life.…”
Section: Introductionmentioning
confidence: 99%